On the use of some tangent cones and sets in vector optimization - Giorgio Giorgi; Cesare Zuccotti (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2012)
For various classes of vector optimization problems, necessary and sufficient optimality conditions are developed in terms of first order tangent cones and second order tangent sets and cones. Additional remarks are also made.
Keywords: 330; Vector optimization problems; effcient points; optimality conditions; tangent cones; tangent sets